Jamming the jamming: Brazilian protests as an illustration of a new politics of consumption. Issue 5 (20th October 2019) - Fontenelle, Isleide Arruda; Pozzebon, Marlei
ABSTRACT: Based on a reflexive and critical analysis of the citizen protests that pervaded Brazilian cities in June 2013, in this article we argue that a significant part of the demonstrators' dissatisfaction took the form of a new politics of consumption with particular characteristics, including the subversion of the culture jamming concept by citizens and by corporations. Our main contribution is to provide the Brazilian protests as an illustration of a new politics of consumption, where 'citizen-consumers' direct their dissatisfaction toward the government using tactics that, historically, were considered counter-hegemonic and directed to the market, as is the case of the culture jamming. Likewise, the corporations present themselves as partners of those citizen-consumers. Mobilizing a dialectical reasoning, our results invite readers to reflect on the ambiguities among politics of consumption and culture jamming, and the challenges they bring to organizations and society.